2020
DOI: 10.1177/1073858420966276
|View full text |Cite
|
Sign up to set email alerts
|

The Translesional Spinal Network and Its Reorganization after Spinal Cord Injury

Abstract: Evidence from preclinical and clinical research suggest that neuromodulation technologies can facilitate the sublesional spinal networks, isolated from supraspinal commands after spinal cord injury (SCI), by reestablishing the levels of excitability and enabling descending motor signals via residual connections. Herein, we evaluate available evidence that sublesional and supralesional spinal circuits could form a translesional spinal network after SCI. We further discuss evidence of translesional network reorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 164 publications
(211 reference statements)
0
14
0
Order By: Relevance
“…Meanwhile, the supralesional EES at C5 did not affect locomotion in the front legs due to supraspinal control. In this study, electrodes were implanted two weeks before SCI at Th9 following the same protocol but with changing the supralesional stimulation site from C5 to Th5 segment with the idea that EES located closer to the injury may facilitate the newly growing axons through the injury, thereby facilitating the formation of a translesional network and promoting interactions between neural networks above and below the injury [ 35 ]. Animals were implanted with stimulating and reference Teflon-coated wire electrodes (AS632, Cooner Wire Company, Chatsworth, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the supralesional EES at C5 did not affect locomotion in the front legs due to supraspinal control. In this study, electrodes were implanted two weeks before SCI at Th9 following the same protocol but with changing the supralesional stimulation site from C5 to Th5 segment with the idea that EES located closer to the injury may facilitate the newly growing axons through the injury, thereby facilitating the formation of a translesional network and promoting interactions between neural networks above and below the injury [ 35 ]. Animals were implanted with stimulating and reference Teflon-coated wire electrodes (AS632, Cooner Wire Company, Chatsworth, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…According to the American Spinal Injury Association, most patients with complete SCI retain some undamaged descending connections, but their spinal cord excitability is severely disrupted, resulting in the loss of function of the intact spinal circuits below the injury (Rossignol and Frigon, 2011 ; Marder et al, 2014 ; Eisdorfer et al, 2020 ). Evidence suggests that neuromodulation technologies can activate the development of sublesional spinal networks, which are isolated from supraspinal commands after SCI, by reestablishing the levels of excitability, and enabling descending motor signals via residual connections (Krupa et al, 2020 ). Whereas the propriospinal networks and the descending reticulospinal commands are putatively the greatest contributors to recovery from anatomically incomplete lesions, recovery from complete lesions is likely due to local lumbar circuit plasticity driven by afferent input (Eisdorfer et al, 2020 ) (see Figure 2A ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…There is evidence that sublesional and supralesional spinal circuits can form a translesional spinal network after SCI (Krupa et al, 2020 ). The existence of this translesional spinal network is one potential mechanism by which electrical stimulation neuromodulation promotes sensorimotor recovery.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical research focused on the various types of SCI has confirmed the promising, beneficial effects of immunomodulatory therapy [2][3][4][5][6], stem cells [7][8][9][10][11], trophic factors [12][13][14][15][16], electric stimulation [17][18][19], axonal regeneration and plasticity; all with the potential to enable an improved functional outcome. In the laboratory setting, several models of SCI are used.…”
Section: Introductionmentioning
confidence: 98%